Pencitraan Hubungan Masyarakat di Indonesia 2001: Mitos dan Realitas dalam Pendekatan Multikultural - Nina Winangsih (MediaTor (Jurnal Komunikasi), 2001)
In global environment, understanding and managing multiculturalism mean recognizing similarities and differences among various cultures and use this cultural diversity to achieve one’s goal. Therefore, it is important to study the impact of cultural contrast upon some practical aspects such as: language; method of communication; cultural as well as management cultures. Culture influences the way in which people interact with one method and has direct impact upon communication patterns. If communication patterns are influenced by culture differences, it is important for public relations managers to be aware of individual behavior. The myth and reality of the Indonesian culture in its unique pluralistic characteristics known as “Bhinneka Tunggal Ika” (Unity through Diversity) represent the Asian society. Dreaming upon the traditional Asian and uniquely Indonesian cultural values, the Indonesian managers of 2001 appear to be successfully working within the cultural boundaries of Asian and Western corporate values. This paper discusses the relationship between cultural and Public Relations practice in Indonesia embracing the trend of 2001—focused on image and possible cultural sensitivity building by means of blending the Asian and Western values to create a synergeticorganizations in practicing Public Relations At 21st centuries.